A rare case of neurosyphilis with oral condyloma lata and fingernail damage - Rui YUE; Nana WANG; Liuyuan WANG; Rongyi CHEN; Ligang YANG (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2024)
A rare case of neurosyphilis with oral condyloma lata and fingernail damage is reported. A 49-year-old male presented with a two-month history of copper-red macules on the palms of both hands and verrucous plaques on the tongue tip for 1 month, and dark shadows on the left eye for 1 week. Dermatological examination revealed uneven and partially thickened nail surfaces of the left thumb and right index finger. The palms were scattered with copper-red macules in the size of mung beans, surrounded by collar-like desquamation. Flat-topped verrucous plaques could be seen on the mucosa of the tongue tip. Hearing was slightly less in the left ear than in the right ear. Corrected visual acuity was 1.0 in the right eye and 0.8 in the left eye. Laboratory tests showed positive for both serum Treponema pallidum particle agglutination (TPPA) (>1∶1 280) and Tolulized red unheated serum test (TRUST) (1∶64). Moreover, the cerebrospinal fluid (CSF) was positive for TRUST(1∶1), TPPA(1∶640) and venereal disease research laboratory (VDRL) (1∶2). The presence of Treponema Pallidum (T. Pallium) in oral verrucous plaque was confirmed by metagenomics next-generation sequencing (mNGS) technology. The diagnosis was neurosyphilis, secondary syphilis (oral flat condyloma). After 2 weeks of treatment with aqua penicillin at a dose of 4 million U q4h, almost all clinical manifestations were improved. Serum TRUST titer was decreased to 1∶8 after 3 months. The follow-up is still ongoing.